Pharmacokinetic Interaction Between Polyphyllin II and Hyperoside Extracts of Rhizoma Paridis and Hypericum Perforatum After Oral Administration in Beagle Dogs - Yin, Xingbin; Qu, Changhai; Zhang, Xiaoyan; Cao, Sali; Feng, Lijun; Yan, Lei; Lin, Longfei; Ni, Jian (Asian Journal of Chemistry, 2012)
A rapid and specific RP-HPLC-UV method was developed for the analysis of polyphyllin II and hyperoside in beagle dog plasma. The analysis was carried out on a Diamonsil C18 (2) reversed-phase column (250 × 4.6 mm, 5 mm) by isocratic elution with acetonitrile and 0.1 % phosphoric acid (50: 50, v/v). The flow rate was 1.0 mL/min and the detection wavelength was set at 203 nm and 360 nm. Linear responses were obtained for polyphyllin II ranging from 3.3333 to 100 μg/mL and hyperoside ranging from 2 to 60 μg/mL. The intra and interday precisions (RSDs) were less than 9.23 and 9.24 % with the accuracy (%) ranging from 89.67 to 107.25 %. The extraction recovery ranged from 84.97 to 91.32 % with RSD less than 7.381 %. Stability studies showed that two compounds were stable in analytical process. In the pharmacokinetic interaction study, present findings indicate that polyphyllin II and hyperoside have a clear effect on the pharmacokinetic behaviour.